Risk indicators for apical periodontitis - Kirkevang L-L, Wenzel A. (Blackwell Synergy, 2003)
The aim of the study was to identify risk indicators for apical periodontitis (AP) in the individual. A parameter was defined as a ‘risk indicator’ when its presence increased the individual’s risk of exhibiting AP. Risk indicators may, but need not be directly associated with the disease